Molecular Characterization of a Patient's Small Cell Carcinoma of the Ovary of the Hypercalcemic Type - Bret Stephens, Stephen P. Anthony, Haiyong Han, Jeffery Kiefer, Galen Hostetter, Michael Barrett, Daniel D. Von Hoff (Journal of Cancer, 2012)
Small cell carcinoma of the ovary of the hypercalcemic type (SCCOHT) is a very rare tumor type that mainly affects young women. We report a 21-year old woman with SCCOHT. The patient initially presented with stage T3AN1MX disease and treated with surgery. The patient then received 8 cycles of multi-agent chemotherapy including cisplatin, bleomycin, cyclophosphamide, doxorubicin, and etoposide. Upon relapse, the patient underwent total abdominal hysterectomy, followed by chemotherapy with gemcitabine. The patient subsequently received radiation therapy and chemotherapy with bevacizumab, irinotecan and docetaxel. She passed away approximately 5 months after the second surgery and with her prior permission an immediate autopsy was performed. We examined the gene expression and copy number profiles of the tumor tissue samples obtained from the autopsy and compared them to normal ovary tissues. Our results indicated that although this tumor did not harbor chromosomal abnormalities nor gene copy number changes, there were significant gene expression changes in a number of genes/pathways. More than 5,000 genes showed significant differential expression in the tumor when compared to normal ovary tissue. Pathway enrichment analysis further identified several pathways/processes including the Vitamin D receptor signaling and the hedgehog signaling pathways to be significantly dysregulated. The gene expression profiling also suggests a number of agents such as pazopanib, bortezomib, 5-azacytidine, and PARP inhibitors as treatment options to possibly explore in future trials against this disease.